Prevalencia y análisis filogenético de hemoparásitos en colonias de Cacicus cela "paucares" Linnaeus, 1758 (Passeriformes: icteridae) - Romero Dávila, Luz Aurora (2016)
Diseases caused by avian hemoparasites are widely distributed in the Americas, causing negative effects on bird health. The objective of the thesis was to determine the prevalence of hemoparasites with respect to geographic location, sex and age in Cacicus cela "paucares"; In addition to performing a phylogenetic analysis to identify the lineages and phylogenetic relationships of hemoparasites in these birds. 89 specimens were captured by mist nets. An aliquot of venous blood was extracted from each specimen and transferred to whatman FTA (Fast Technology for Analysis of Nucleic Acids) cards. The DNA was extracted by standard procedures and by PCR a 478 bp fragment of the cytochrome b codating gene was amplified, this amplicon was purified and sequenced with standard methods. There was a high prevalence of avian hemoparasite infections in the colonies studied (from 87% to 100%). With the sequence obtained, homologs were searched in a database and phylogenetic analysis was performed, with a total of 5 lineages belonging to Plasmodium spp., Of which 4 were first discovered in this work (Lineages “64”, “68 "," 211 "," 12 "). In conclusion, there is a high prevalence of hemoparasites in Cacicus cela "paucares", females being more susceptible than males to be infected. Likewise, juveniles mostly parasitized than chicks and adults. Lineage "59" was the most frequent, being found in all sampling areas.